Eksperimen Kualitas Ketahanan Bakar Pada Briket Serbuk Kayu Menggunakan Metode Taguchi - Muttaqin, Muhammad Faishal Jundana; Fredynanta Ginting S; Dimas Ardianto; Hizkia Debitus D. J; Hafidzul Muparrij (Jurnal Serambi Engineering, 2025)
This study discusses an experimental approach to producing briquettes from sawdust, with the aim of evaluating their burn durability using the Taguchi method. This method was employed to identify and optimize the key factor combinations involved in briquette manufacturing. The experiment tested three main factors—charcoal composition, tapioca flour (as a natural binder), and water (as a solvent)—each at two distinct levels. Four experimental combinations were conducted based on the L4 (2^3) orthogonal array, with each experiment replicated three times to ensure data reliability. The experimental results revealed that the tapioca flour factor (B) had the greatest influence on burn durability, followed by charcoal (A), while water (C) had a negligible effect. ANOVA results indicated that factor B contributed 12.52%, factor A 4.04%, and factor C only 0.01%, with the remaining 83.43% attributed to experimental error. The optimal combination for achieving the best burn durability was A1 (80 gr of charcoal), B1 (16 gr of tapioca flour), and C1 (120 ml of water). These findings offer practical implications for the development of efficient and environmentally friendly biomass-based alternative energy, and demonstrate the effectiveness of the Taguchi method in quality optimization processes.